KELF'S super secretary a feasibility study on secretarial services - Tan, Alfred; Tan, Kerwin; Uy, Edward (Diliman, Quezon City College of Engineering, 1993)
This feasibility study focused on the feasibility of "KELF's Super Secretary", a proposed service corporation which is geared towards providing its users with state-of-the-art office amenities and a professional staff at a competitive price. In the marketing aspect of this feasibility study, the various services to be offered by KELF were determined through an in-depth analysis of the demand and supply of its lone competitor. Also, through a survey questionnaire, the proponents of this study were able to determine the customer preferences and the predicted future demand for the initial year of KELF's operation. A favorable forecast of its future demand established the fact that the project on this aspect is feasible. The technical study focused on the systems and the methods used for each of the services to be offered by KELF in order to provide efficient and high quality services to its clients. Lay outing, selection of equipment, service procedures and capacity planning were just a few of the main concerns of this section. Like the marketing section, the technical study is feasible. The financial study details the profitability of the service company. Financial statements required such as the cash flow, income statement and the balance sheet were projected up to 1998, the fifth year of KELF's operation. Financial evaluation techniques and measures were also used to ascertain its viability. After utilizing all the necessary financial tools, the financial study simply reaffirms the feasibility of the proposed service corporation. In the social profitability analysis, the group determined the socio-economic effects of establishing the firm. Also, a detailed cost-benefit analysis showed various positive socio-economic contribution of the project such as the additional tax revenues to be received by the government. Furthermore, additional employment will be generated by the project. Thus, the study, in its entirety, is feasible and workable. It is in this light that the proponents of this feasibility study endorse this study for the advancement of the professional secretarial services in the Philippines.
Feasibility Study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management
Keywords: KELF's Super Secretary; Home-based business support services; Participatory monitoring and evaluation (Project management)